Keefektifan Konseling Kelompok Cognitive Behavior untuk Meningkatkan Konsep Diri Positif Siswa SMP - Rias Wulan Mustiani (Indonesian Journal of Educational Counseling, 2019)
EFFECTIVENESS OF COGNITIVE BEHAVIOR COUNSELING GROUP TO INCREASE THE POSITIVE SELF CONCEPT OF MIDDLE SCHOOL STUDENTS. This study aims to test the effectiveness of counseling cognitive behavior group to improve the positive self-concept of students in junior high. This research uses a pre-experimental pretest type posttest one-group design. The data analysis used is paired test of T-test, to see the change of positive self-concept level in the experimental group between pretest and posttest by looking at t-table price at degrees of freedom (dk), that is the magnitude is N-1, significant α = 0,05 (95%) then got t-table. = 1.782 assuming if t count> t-table then Ha “received.” The results of data analysis of the responses of respondents about positive self-concept show positive self-concept students before intervention is in the category of being, and there is still a low category of 13 respondents. As for after the treatment, based on the posttest results, indicate the criteria of self-concept positive students, no one is in a low category. From the test result using T-Test, it is proved that counseling group of cognitive behavior is effective to improve the positive self-concept of junior high school students, because the value of t count> t table (7.597> 1.782), then the hypothesis that the writer proposed in the form of alternative hypothesis (Ha) the effectiveness of counseling cognitive behavior group to improve the positive self-concept of junior high school students, Ha “accepted”.